THE DYNAMICS OF PRODUCT VARIANTS IN SUSTAINING BRAND IDENTITY AND EMOTIONAL RELATIONSHIPS - Didit Darmawan; Nur Aini Dian Novita (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2026)
This study conducts a literature review on the role of product variant exploration in maintaining brand relevance. It addresses two main issues: the tension between innovation and brand identity purity, and the challenge of building emotional bonds amidst changing consumer behavior. The analysis is structured into two parts. First, it examines how product variants influence consumer perception of brand identity clarity, finding that alignment with core values reinforces identity while excessive divergence risks dilution. Second, it explores how variants foster relevant emotional connections by enabling personal expression, becoming part of consumer rituals, and accumulating shared memories. The study concludes that effective variant management requires a strategic balance between exploration and identity preservation. Product variants are not merely tools for market expansion but critical instruments for sustaining a dynamic and meaningful dialogue between the brand and its consumers. Theoretical implications suggest expanding brand equity frameworks to include dynamic meaning-making, while practical implications emphasize disciplined portfolio evaluation and the importance of involving loyal consumers in the innovation process.